2018
DOI: 10.1111/jpi.12502
|View full text |Cite
|
Sign up to set email alerts
|

Copper chelators promote nonamyloidogenic processing of AβPP via MT1/2/CREB‐dependent signaling pathways in AβPP/PS1 transgenic mice

Abstract: Copper is essential for the generation of reactive oxygen species (ROS), which are induced by amyloid‐β (Aβ) aggregation; thus, the homeostasis of copper is believed to be a therapeutic target for Alzheimer’s disease (AD). Although clinical trials of copper chelators show promise when applied in AD, the underlying mechanism is not fully understood. Here, we reported that copper chelators promoted nonamyloidogenic processing of AβPP through MT1/2/CREB‐dependent signaling pathways. First, we found that the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Furthermore, Cu 2+ significantly affects the amyloid cascade, by which it interacts with APP through a Cu 2+ -binding domain [49]. Copper chelator can inhibit the activity of β-secretase [50]. In a preclinical AD model, small amounts of copper in drinking water can induce Aβ accumulation and significantly retard the learning ability [51].…”
Section: Coppermentioning
confidence: 99%
“…Furthermore, Cu 2+ significantly affects the amyloid cascade, by which it interacts with APP through a Cu 2+ -binding domain [49]. Copper chelator can inhibit the activity of β-secretase [50]. In a preclinical AD model, small amounts of copper in drinking water can induce Aβ accumulation and significantly retard the learning ability [51].…”
Section: Coppermentioning
confidence: 99%
“…Our previous study has showed that H3R antagonist activates autophagy and protects against cerebral ischemic injury (Yan et al, 2014). In addition, activation of H3R downstream signaling CREB, which is involved in improving cognitive dysfunction and Aβ pathology in AD (Wang et al, 2018; Yin et al, 2016), could also up‐regulate autophagy (Chong et al, 2018; Liu et al, 2019; Seok et al, 2014). Nevertheless, whether CREB‐mediated autophagy is involved in the alleviated cognitive deficit and Aβ pathology by H3R antagonist in AD remains undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…After the samples returned to room temperature, they were diluted 20 times with 0.1% nitric acid (Sigma). Then, the samples were measured using AAS (ZEEnit700P, Analytikjena, Germany) as previously described [ 58 ].…”
Section: Methodsmentioning
confidence: 99%